Strategic Organizational Communication for Synergy: Post-Acquisition Integration of Parent and Subsidiary Companies - Destria, Chelma; Ramonita, Latifa (Ilomata International Journal of Social Science, 2025)
This study examines the role of strategic organizational communication in fostering synergy between parent and subsidiary companies post-acquisition, using PT Bank Negara Indonesia (BNI) and PT Bank Hibank Indonesia (hibank) as a case study. As digital banking services for MSMEs expand, effective internal and external communication becomes crucial in mergers and acquisitions. While prior studies focus on structural integration, this research highlights the strategic role of communication by applying the ADKAR model for change management and Integrated Marketing Communication (IMC) for branding strategies. Through a qualitative approach involving in-depth interviews and secondary data analysis, key communication challenges and strategies are identified. Findings indicate that both formal and informal communication are critical for integration, yet internal communication gaps create uncertainty among employees. The ADKAR model reveals the need for stronger awareness, desire, and reinforcement efforts to enhance adaptation. Externally, IMC strategies support brand identity, but inconsistencies in hibank’s affiliation with BNI weaken public perception. Transparent and participatory internal communication improves employee engagement, while refined external communication ensures brand consistency. Future research should quantify communication effectiveness in M&A contexts to strengthen corporate synergy.